Exploring the Distribution of ABO and Rhesus Blood Groups among Beta Thalassemia Patients in Punjab, Pakistan: A Cross-Sectional Study - Muhammad Waqas; Mahpara Anwar; Razia Bashir; Humera Ambreen; Khadija Munir; Maham Iqbal; Muhammad Arshad (Kashmir Journal of Science)
Background: Beta thalassemia is a genetic hematological disorder characterized by impaired or absent hemoglobin synthesis. It is affecting millions around the world, posing them for a lifelong blood transfusion. People have different blood types based on genetically determined antigens that play a vital role in transfusion safety. Blood group antigens show strong correlation with many diseases like Diabetes, immune disorders, cancers etc.